SOSIALISASI SPORT RECOVERY PADA KSR PMI UNIT UNJ - Ruliando Hasea Purba; Mansur Jauhari; Tridinda Aprilia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2022)
Abstract. The KSR-PMI unit of UNJ is one of the fields to channel talents in organizations and communities that often serve in the health sector. The purpose of holding this event is to increase the knowledge of sports recovery KSR-PMI units of UNJ. 55 members of the KSR-PMI unit of UNJ participated in this activity. The method of implementing this activity begins with the provision of Pre- Test questions, then the explanation of the material, followed by a discussion, after which the Post-Test questions are given, and then data analysis is carried out using IBM SPSS Statistics 26 and Ms Excel. The results of the data analysis showed that the post-test mean (26.63) > the pre-test mean (58.45). Participants experienced an increase in knowledge about recovery by 119% after participating in this activity. The motivation and enthusiasm of the participants are very high marked by activeness during discussions. Efforts that can be made by members of the Indonesian Red Cross Voluntary Corps (KSR PMI) UNIT UNJ after this activity, namely being able to take preventive measures so that the potential for injury decreases and have sufficient knowledge to be able to implement it to the community and provide sports recovery information to the community. Abstrak. KSR-PMI unit UNJ adalah salah satu bidang untuk menyalurkan bakat dalam organisasi maupun kemasyarakatan yang sering bertugas di bidang Kesehatan. Tujuan diadakannya acara ini yaitu untuk meningkatkan pengetahuan sport recovery KSR-PMI unit UNJ. Anggota KSR-PMI unit UNJ yang mengikuti kegiatan ini sebanyak 55 orang. Metode pelaksanaan kegiatan ini yaitu diawali dari pemberian soal Pre-Test, lalu penjelasan materi, dilanjutkan diskusi, setelah itu diberikan soal Post-Test, lalu dilakukan analisis data dengan menggunakan IBM SPSS Statistics 26 dan Ms. Excel. Hasil dari analisis data menunjukkan bahwa mean post-test (26,63) > mean pre-test (58,45). Peserta mengalami peningkatan pengetahuan tentang recovery sebesar 119% setelah mengikuti kegiatan ini. Motivasi dan antusiasme dari para peserta sangat tinggi ditandai dengan keaktifan saat diskusi. Upaya yang dapat dilakukan oleh anggota Korps Sukarela Palang Merah Indonesia (KSR PMI) Unit UNJ setelah kegiatan ini, yaitu dapat melakukan tindakan pencegahan agar potensi cedera menurun serta memiliki pengetahuan yang cukup untuk dapat mengimplementasikannya kepada masyarakat dan memberi informasi sport recovery kepada masyarakat.